Development of Augmented Reality–Based Learning Media for Historical Object Recognition at Deli Serdang Museum - Hermansyah; Wirda Fitriani; Mai Sarah (CV Raskha Media Group, 2025)
History learning in museums is generally still dominated by conventional information delivery through text labels and verbal explanations, which tends to be less engaging for the digital generation. This study aims to develop and evaluate the feasibility of an Augmented Reality (AR)–based learning media application for introducing historical objects at the Deli Serdang Museum on Android devices. A research and development (R&D) approach was employed using the Waterfall software development model, consisting of requirements analysis, design, implementation, and testing. Data were collected through literature review, observation and documentation of museum collections, and interviews with museum staff. The system was designed using UML and implemented with Unity, Vuforia, and 3D object modelling. Functional testing was carried out using black box testing, while an initial feasibility test involved 10 respondents who completed a questionnaire on system performance and user experience. The results show that all core features (marker detection, 3D object display, rotation and zoom functions, and menu navigation) operated according to specification without critical errors. Most respondents stated that the application is easy to use, visually attractive, and helpful in understanding the museum’s historical collections. Therefore, the developed AR application is considered feasible as a supplementary learning medium at the Deli Serdang Museum and has the potential to be extended to other museum contexts